Growth and deformation simulation of aluminum bronze grains produced by electron beam additive manufacturing - Nikonov, Anton Yu; Lychagin, Dmitry V.; Bibko, Artem A.; Novitskaya, Olga S. (Metals)
When working out 3D building-up modes, it is necessary to predict the material properties of the resulting products. For this purpose, the crystallography of aluminum bronze grains after electron beam melting has been studied by EBSD analysis methods. To estimate the possibility of sample form changes by pressure treatment, we simulated structural changes by the method of molecular dynamics during deformation by compression of individual grains of established growth orientations. The analysis was carried out for free lateral faces and grain deformation in confined conditions. Simulation and experiments on single crystals with free lateral faces revealed the occurrence of stepwise deformation in different parts of the crystal and its division into deformation domains. Each domain is characterized by a shear along a certain slip system with the maximum Schmidt factor. Blocking the shear towards the lateral faces leads to selectivity of the shear along the slip systems that provide the required shape change. Based on the simulation results, the relationship between stress-strain curves and structural characteristics is traced. A higher degree of strain hardening and a higher density of defects were found upon deformation in confined conditions. The deformation of the columnar grains of the built material occurs agreed with the systems with the maximum Schmidt factor.